Targeting TREM-1 Signaling in the Presence of Antibiotics is Effective Against Streptococcal Toxic-Shock-Like Syndrome (STSLS) Caused by Streptococcus suis - Yang, Chao; Zhao, Jianqing; Lin, Lan; Pan, Shan; Fu, Lei; Han, Li; Jin, Meilin; Zhou, Rui; Zhang, Anding (Frontiers in Cellular and Infection Microbiology, 2015)
Streptococcus suis (S. suis), a major swine pathogen, is also a severe threat to human health. Infection with highly virulent strains of S. suis can cause human Streptococcal toxic-shock-like syndrome (STSLS), which is associated with high serum pro-inflammatory cytokine levels and a high mortality rate. Our previous study indicated that highly virulent S. suis infection could activate the TREM-1 signaling pathway, which promotes host clearance of S. suis during early infection. However, it remained to be elicited whether TREM-1 signaling could be a target against STSLS in the presence of antibiotic. In the present study, mice were infected with a highly virulent S. suis strain and then treated with rTREM-1 (the recombinant extracellular domain of TREM-1) to block TREM-1 signaling, antibiotics, both rTREM-1 and antibiotics, or PBS. The survival rates, clinical signs, serum IL-1β and TNF-α levels, and serum bacterial loads were evaluated. Treatment with rTREM-1 could aggravate the outcome of infection as described previously. Although the conventional treatment with antibiotics contributed to effective S. suis clearance, it did not improve survival significantly. In comparison, due to the reduction of the exaggerated pro-inflammatory response, treatment combined with rTREM-1 and antibiotics not only led to efficient bacterial clearance but also alleviated inflammation. In conclusion, TREM-1 signaling contributed to severe inflammatory response and benefited S. suis clearance. Therefore, blocking TREM-1 signaling could still be a target for the treatment of STSLS in the presence of antibiotics.